Improving the Integrity of Pharmaceutical Serialization with Enterprise Technologies - Hariprasad Mandava (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Medical devices and pharmaceutical drugs undergo packaging procedures to ensure their stability and integrity remain intact throughout post-production shipping and storage, prior to their clinical utilization. Throughout delivery and storage, the packaging may interact either directly or indirectly with the drug product or medical device, potentially leading to chemical reactions between the two. The role of packaging is paramount in ensuring success, safeguarding the product, and facilitating its sale. Similar to other items found in supermarkets, prescription pharmaceuticals necessitate packaging that addresses various needs, including security, promptness, safety, product identity, quality assurance, patient well-being, and product excellence. Packaging represents both a scientific and artistic endeavour, involving the consideration of numerous factors, beginning with the fundamental design and technology utilized to package the product securely, while also ensuring its protection, presentation, and compliance with manufacturing standards during transportation, storage, and consumption. To uphold the physiochemical, biological, and chemical stability of drugs, packaging professionals design containers capable of withstanding the pressures encountered during supply and shipping processes. Enhancements in the field of prescription drug development have long emphasized the importance of packaging expertise. This serialization process is crucial for bolstering drug security within the supply chain while maintaining drug quality, thereby minimizing the risk of counterfeit drugs infiltrating the distribution network.